Corpus-Based Analysis of the Meaning and Translation of The Arabic Word “Ghurfah” in Islamic Discourse - Jibreel, Ibrahim; Al-Shawki, Abdulmalik; Almuslimi, Arwa; Mukarram, Ebtesam; Al-shawfi, Bushraa; Nasher, Mona; Al-absi, Wafa'a (Democratic Arabic Center for Strategic, Political and Economic Studies (DAC), 2024)
This research aims to identify the meaning of the polysemous and homonymy word Ghurfah (غرفة) in Arabic language. In addition, it investigates the word Ghurfah (غرفة)in Arabi Corpus. Besides, it sheds light on its translation in the Holy Quran. The descriptive methodology is followed utilizing a content-based analysis. It is found that the word Ghurfah (غرفة) has repeated in the Holy Quran 5 times with two different meanings. viz taking quality of water and place in paradise. In Arabi Corpus, it is found that the most common meaning of the word Ghurfah (غرفة) is place, followed by virtual or metaphorical meaning, a place in paradise and lastly to take a quality of water respectively. Moreover, the most common meaning used for the word Ghurfah (غرفة) is the room of four walls, a room according to long man dictionary (apart inside of a building that has its own wall, floor, and ceiling). The researchers clarified its interpretations according to the two interpreters Abdallah Youssef and Shaker. They reflected the two meanings with slight differences in their translations.
Keywords: Arabi Corpus; Corpus-Linguistics; Ghurfah; Homonymy; Polysemy